Chiklit - et genresignalement - Annemette Hejlsted (The Royal Danish Library, 2009)
Chicklit - a genre descriptionChicklit is one of the most controversial genres of the last decade. This article interprets the kinship terms of the genre by analysing selected named chicklit novels from different points of view, and gives suggestions as to the ideas and aesthetic strategies of the genre. By descriptions of protagonists, plot, narrator and style and their references to shapes of mass culture a kinship with postmodernist fiction is depicted. The article point out that chicklit foregrounds questions about gender constructions. Through settings of everyday performance and literary strategies of the comic and the ironic the genre reactivates agendas of middleclass feminism. In conclusion chicklit seems to be a new kind of post feminist literature.